2014
DOI: 10.1002/adhm.201400307
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Macromolecular Prodrugs Inhibit Expression of the Hepatitis C Virus Genome in the Host Cells

Abstract: Efficacious, potent, and at the same time nontoxic macromolecular prodrugs of ribavirin are designed taking advantage over prodrug activation by the intracellular milieu. Activity of these prodrugs is illustrated in the cells hosting hepatitis C virus replication and also in the cells implicated in the inflammatory response to the viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…We note that data in Fig. 7 are rather similar to the drug release data collected in our prior studies via HPLC [43,46,62] and this serves to validate the established herein NMR-based approach to monitor drug release. 1 H NMR based method to quantify drug release was applied to the macromolecular prodrugs based on other polyanions as well as a nonionic carrier, PHPMA, Fig.…”
Section: Drug Release Kineticssupporting
confidence: 76%
See 3 more Smart Citations
“…We note that data in Fig. 7 are rather similar to the drug release data collected in our prior studies via HPLC [43,46,62] and this serves to validate the established herein NMR-based approach to monitor drug release. 1 H NMR based method to quantify drug release was applied to the macromolecular prodrugs based on other polyanions as well as a nonionic carrier, PHPMA, Fig.…”
Section: Drug Release Kineticssupporting
confidence: 76%
“…We also experimentally confirmed the link between ribavirin and the synthesis of nitric oxide in macrophages, with relevance to the treatment of hepatitis [42]. Key to successful delivery of ribavirin using MP was the development of a disulfide-containing linker that releases the drug from the prodrug upon cell entry [43].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…The amount of 3TC prodrug released in the absence of a thiol trigger was very similar to values reported for polymers consisting of ribavirin when incubated in phosphate buffer for 48 hours. 48 Furthermore, 25 control experiments performed at pH 5.8 in the presence and absence of GSH showed that only ~10% of 3TC was released. These results indicated that the 3TC conjugated to the polymer via the disulfide SIL was stable at pH 7.4 in the absence of GSH as well as at pH 5.8 even in the presence of 5 mM GSH ( Figure S16).…”
Section: Lamivudine Release From Polymersmentioning
confidence: 97%